Formed catalyst for flue gas denitration at ultra-low temperature based on 3D printing and preparation method thereof
Patent Information
- Application Number
- CN202510739892.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-04
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2045-06-04
AI Technical Summary
选择性催化还原(SCR)技术具有高效性和成熟性的优势,已成为脱硝的主要选择,但目前传统SCR催化剂依赖陶瓷或金属载体(如堇青石),通过挤压成型工艺制备蜂窝结构,但这种蜂窝状的催化剂存在结构限制、稳定性差以及制备成本高等问题
[0017]根据本发明第三方面的反应器,包括固定床或流化床和根据第二方面所述的催化剂,所述催化剂用于填装在所述固定床或所述流化床中。
Smart Images

Figure CN120754841B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of catalyst technology, and in particular to a 3D-printed ultra-low temperature flue gas denitrification molding catalyst and its preparation method. Background Technology
[0002] Nitrogen oxides (NO) x Nitrogen oxides (NOx) are a major air pollutant that poses a serious threat to the ecological environment and human health. Selective catalytic reduction (SCR) technology has the advantages of high efficiency and maturity, and has become the main choice for denitrification. However, current traditional SCR catalysts rely on ceramic or metal supports (such as cordierite) to prepare honeycomb structures through extrusion molding. However, such honeycomb catalysts have problems such as structural limitations, poor stability, and high preparation costs. Summary of the Invention
[0003] The present invention aims to at least solve one of the technical problems existing in the prior art. To this end, the present invention proposes a method for preparing a 3D-printed ultra-low temperature flue gas denitrification catalyst. This method can prepare a particulate catalyst with good stability and wide applicability to different reactors.
[0004] This invention also proposes a catalyst for ultra-low temperature flue gas denitrification based on 3D printing.
[0005] The present invention also proposes a reactor having the above-mentioned catalyst.
[0006] According to a first aspect of the present invention, a method for preparing a 3D-printed ultra-low temperature flue gas denitrification catalyst includes: step S1, preparing a metal oxide precursor; step S2, preparing a mixed slurry based on the metal oxide precursor, an inorganic binder, an organic binder, an additive, and a solvent; step S3, printing the mixed slurry into a printed preform using 3D printing direct-write molding technology; and step S4, drying and calcining the printed preform to obtain the catalyst.
[0007] According to the preparation method of the ultra-low temperature flue gas denitrification catalyst based on 3D printing of the present invention, the catalyst material is printed into granular catalyst by 3D printing technology, which can ensure the uniform distribution of active components, thereby improving the catalytic performance and stability of the catalyst. At the same time, the granular catalyst has extremely high stability, not only remaining stable under high-speed airflow purging, but also resisting external impacts and not easily broken, thus enabling the catalyst to adapt to various reaction conditions and process requirements, improving the catalyst's applicability. In addition, the catalyst preparation using 3D printing direct writing technology not only provides unprecedented flexibility in manufacturing complex structures and customized products, but also significantly shortens the research and development cycle and reduces production costs.
[0008] According to some embodiments of the present invention, the mixed slurry, by weight, comprises: 70-90 parts of metal oxide precursor; 2-5 parts of inorganic binder; 5-15 parts of organic binder; 2-5 parts of additives; and 1-5 parts of adhesive solvent.
[0009] According to some embodiments of the present invention, the inorganic binder is one or more of alumina sol, silica sol, sodium silicate, halloysite nanotubes, bentonite, and kaolin; and / or, the organic binder is one or more of polyvinyl alcohol, polyethylene glycol, polyacrylamide, carboxymethyl cellulose, and starch; and / or, the additive is one or more of guar gum powder, graphite, polytetrafluoroethylene, glycerol, glass fiber, and activated carbon; and / or, the adhesive solvent is one or more of oxalic acid, citric acid, acetic acid, and ammonia.
[0010] According to some embodiments of the present invention, the metal oxide precursor, the inorganic binder, the organic binder, the additives, and the adhesive solvent are placed in a ball mill to prepare a mixed slurry, the ball milling speed is 200 r / min-500 r / min, and the ball milling time is 10 min-30 min.
[0011] According to some embodiments of the present invention, the drying temperature of the printed preform is 50 ℃-120 ℃, and the drying time is 2h-8h; the calcination temperature of the printed preform is 300℃-600 ℃, and the calcination time is 2-8h.
[0012] According to some embodiments of the present invention, step S1 includes: step S11, preparing an alkaline solution containing an alkali metal or an alkaline earth metal; step S12, adding a metal oxide support to the alkaline solution and stirring to obtain a mixture; step S13, placing the mixture in a hydrothermal reactor to carry out a hydrothermal reaction to obtain a reactant; and step S14, filtering and drying the reactant to obtain a metal oxide precursor.
[0013] According to some embodiments of the present invention, the alkaline solution of the alkali metal or alkaline earth metal is one or more of sodium hydroxide solution, potassium hydroxide solution, rubidium hydroxide solution, cesium hydroxide solution, strontium hydroxide solution, and barium hydroxide solution; and / or, the metal oxide support is one or more of manganese oxide, manganese dioxide, manganese trioxide, manganese tetroxide, and manganese pentoxide.
[0014] According to a second aspect of the present invention, a 3D-printed ultra-low temperature flue gas denitrification catalyst is prepared by the preparation method described in the first aspect of the present invention.
[0015] The 3D-printed ultra-low temperature flue gas denitrification catalyst of the present invention, prepared by the above-mentioned method, can ensure the uniform distribution of the active components of the catalyst, thereby improving the catalytic performance and stability of the catalyst; at the same time, it can also make the catalyst have extremely high stability, not only remaining stable under high-speed airflow purging, but also resisting external impacts and not easily broken, thus enabling the catalyst to adapt to various reaction conditions and process requirements, and improving the applicability of the catalyst.
[0016] According to some embodiments of the present invention, the catalyst is a spherical, cylindrical, flake-shaped or columnar particle, and / or the diameter of the catalyst is 2 mm-9 mm, and / or the length of the catalyst is 5 mm-10 mm.
[0017] According to a third aspect of the invention, a reactor comprises a fixed bed or a fluidized bed and a catalyst according to a second aspect, the catalyst being used to pack the fixed bed or the fluidized bed.
[0018] According to the reactor of the present invention, by filling it with the above-mentioned catalyst, the stability and reliability of the entire process can be improved, and the frequency of catalyst replacement can be reduced, thereby reducing maintenance costs.
[0019] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Attached Figure Description
[0020] Figure 1 This is a flowchart of a method for preparing a 3D-printed ultra-low temperature flue gas denitrification molding catalyst according to an embodiment of the present invention; Figure 2 This is a flowchart of the preparation of metal oxides according to an embodiment of the present invention; Figure 3 This is an overall flow chart of the preparation method of the 3D-printed ultra-low temperature flue gas denitrification molding catalyst according to an embodiment of the present invention. Detailed Implementation
[0021] Embodiments of the present invention are described in detail below. Examples of these embodiments are illustrated in the accompanying drawings, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention.
[0022] The following is for reference. Figures 1-3 A method for preparing a 3D-printed ultra-low temperature flue gas denitrification catalyst according to an embodiment of the first aspect of the present invention is described.
[0023] like Figure 1 and Figure 3 As shown, the preparation method of the 3D-printed ultra-low temperature flue gas denitrification catalyst according to an embodiment of the present invention includes: Step S1: Prepare metal oxide precursor; it should be noted that the metal oxide precursor is a modified metal oxide, which has good low-temperature activity and oxidation performance.
[0024] Step S2 involves preparing a mixed slurry based on a metal oxide precursor, an inorganic binder, an organic binder, additives, and a solvent. It should be noted that the inorganic binder is mainly used to ensure the structural stability of the catalyst; the organic binder is mainly used to improve the plasticity and wear resistance of the slurry during molding and the wear resistance of the catalyst after molding; the additives are mainly used to reduce friction and improve the flowability of the extruded preform; and the solvent is mainly used to adjust the pH of the mixed slurry, thereby providing a suitable chemical environment for the organic binder to better exert its adhesive effect and molding performance.
[0025] Step S3: The mixed slurry is printed into a shape using 3D printing direct writing technology to obtain a printed preform. It should be noted that 3D printing direct writing technology is an additive manufacturing process based on the principle of extrusion. It constructs a three-dimensional structure by precisely controlling the extrusion of materials.
[0026] Step S4 involves drying and calcining the printed preform to obtain a monolithic granular catalyst. It should be noted that in the 3D printing process, the drying step primarily removes solvents from the printed part, thus improving the final structural stability of the catalyst; it also serves as a preliminary curing agent, increasing the physical strength of the printed preform and facilitating its transfer to the calcination location. Calcination, a process conducted at high temperatures, is mainly used to remove organic binders or other impurities from the 3D printed object; simultaneously, calcination densifies the material structure, enhancing its hardness, wear resistance, and other mechanical properties.
[0027] In existing technologies, traditional SCR catalysts mainly rely on ceramic or metal supports (such as cordierite) to prepare honeycomb structures through extrusion molding. However, this molding method has problems such as structural limitations, poor low-temperature activity, and high preparation costs.
[0028] In this application, a preform is printed using 3D printing direct-write molding technology, and then dried and calcined in air to obtain a monolithic particulate catalyst. 3D printing technology, as an emerging manufacturing process, can rapidly create complex three-dimensional entities by adding materials layer by layer. It has significant advantages in manufacturing complex structures, customized products, and rapid prototyping. Therefore, using 3D printing direct-write molding technology to prepare catalysts not only provides unprecedented flexibility in manufacturing complex structures and customized products, but also significantly shortens the R&D cycle and reduces production costs. Furthermore, preparing particulate catalysts using 3D printing technology not only achieves precise and uniform distribution of active components, but also allows for flexible control of microstructure and macromorphology, thereby significantly improving catalytic performance, stability, and engineering adaptability. In addition, compared to traditional honeycomb denitrification catalysts, particulate catalysts have no pores, thus exhibiting extremely high stability. They can remain stable under high-speed airflow purging and resist external impacts without easily breaking.
[0029] According to the preparation method of the 3D-printed ultra-low temperature flue gas denitrification catalyst according to embodiments of the present invention, the catalyst material is printed into granular catalyst using 3D printing technology, which can ensure the uniform distribution of active components, thereby improving the catalytic performance and stability of the catalyst. At the same time, the granular catalyst has extremely high stability, not only remaining stable under high-speed airflow purging, but also resisting external impacts and not easily broken, thus enabling the catalyst to adapt to various reaction conditions and process requirements, improving the catalyst's applicability. In addition, the catalyst preparation using 3D printing direct writing technology not only provides unprecedented flexibility in manufacturing complex structures and customized products, but also significantly shortens the research and development cycle and reduces production costs.
[0030] According to some embodiments of the present invention, the mixed slurry, by weight, comprises: 70-90 parts of a metal oxide precursor; 2-5 parts of an inorganic binder; 5-15 parts of an organic binder; 2-5 parts of additives; and 1-5 parts of a solvent. For example, if the mixed slurry comprises 100 parts, the metal oxide may be 90 parts, the inorganic binder may be 2 parts, the organic binder may be 5 parts, the additives may be 2 parts, and the solvent may be 1 part. That is, by weight, the total components of the metal oxide precursor, inorganic binder, organic binder, additives, and solvent are 100 parts.
[0031] Among them, the metal oxide precursor is the main component of the catalyst, which is mainly used to ensure the oxidation performance and low-temperature activity of the catalyst, so that the catalyst has excellent low-temperature nitrogen oxide removal performance; the inorganic binder is mainly used to ensure the structural stability of the catalyst; the organic binder is mainly used to improve the plasticity and wear resistance of the slurry during the molding process and the wear resistance of the catalyst after molding; the additives are mainly used to reduce friction and improve the flowability of the extruded preform; the adhesive is mainly used to adjust the pH of the mixed slurry, thereby providing a suitable chemical environment for the organic binder, so that it can better exert its adhesive effect and molding performance.
[0032] According to some embodiments of the present invention, the inorganic binder is one or more selected from alumina sol, silica sol, sodium silicate, halloysite nanotubes, bentonite, and kaolin. Specifically, the inorganic binder may be one or more of the above-mentioned binders, and the specific selection can be adjusted according to the specific application requirements to achieve the best effect and improve the structural stability of the final formed catalyst.
[0033] Specifically, aluminum sol is a stable suspension formed by dispersing alumina particles in water or other solvents. Aluminum sol exhibits good thermal stability and chemical inertness. In catalyst preparation, aluminum sol is often used as a binder, enhancing the bonding force between catalyst particles, improving the high-temperature resistance of the finished product, promoting the uniform distribution of active components, and helping to maintain the porous structure of the catalyst.
[0034] Silica sol is composed of fine silica particles and is typically transparent or translucent. It exhibits excellent weather resistance and chemical resistance. When used as a binder, silica sol provides good mechanical strength and chemical stability. Furthermore, due to its unique microporous structure, silica sol can improve catalyst diffusion performance and increase specific surface area, thereby enhancing catalytic efficiency.
[0035] Sodium silicate is a common inorganic binder that readily dissolves in water to form an alkaline solution. During heating, it dehydrates and hardens, forming a robust structure. In catalyst preparation, sodium silicate not only acts as a binder but also adjusts the pH value of the catalyst, influencing the state of the active components.
[0036] Halloysite nanotubes are naturally occurring nanomaterials with a hollow tubular structure and an inner diameter typically tens of nanometers. This unique morphology endows halloysite nanotubes with an extremely high aspect ratio and a large specific surface area. As a novel binder, halloysite nanotubes can not only significantly enhance the mechanical strength of catalysts but also accommodate more active components through their internal space, thereby improving the overall performance of the catalyst.
[0037] Bentonite, primarily composed of montmorillonite, possesses strong water absorption, swelling, and ion exchange capabilities. It can rapidly swell in water to form a gel-like substance. In catalyst preparation, bentonite can be used as a binder and thickener to help immobilize active components. Simultaneously, its excellent ion exchange properties help regulate the pH of the catalyst surface, thereby influencing the selectivity and activity of the catalytic reaction.
[0038] Kaolin is a layered silicate mineral with low cation exchange capacity and good thermal stability. As a binder, kaolin is mainly used to enhance the mechanical strength and thermal stability of catalysts. Furthermore, kaolin can also interact with active components to alter the surface properties of catalysts and optimize their catalytic performance.
[0039] According to some embodiments of the present invention, the organic binder is one or more selected from polyvinyl alcohol, polyethylene glycol, polyacrylamide, carboxymethyl cellulose, and starch. Specifically, the organic binder may be one or more of the above-mentioned binders, and the specific selection can be adjusted according to the specific application requirements to achieve the best effect and improve the structural stability and wear resistance of the final molded catalyst.
[0040] Polyvinyl alcohol (PVA) possesses excellent film-forming properties, strong adhesion, and is non-toxic and environmentally friendly. As an organic binder in the catalyst preparation process, it helps to improve the strength of the preform and increase the bonding force between particles. Polyethylene glycol (PEG) can regulate the fluidity of the slurry and has high plasticity, which can improve the rheological properties of extrusion or printing and reduce friction. Polyacrylamide has extremely strong flocculation and thickening properties, which can enhance the suspension stability of the mixed solution and prevent sedimentation. Carboxymethyl cellulose (CMC) has good adhesion, water retention, and dispersibility, and can play a dual role of adhesion and stabilization. Starch is a green binder that can provide preliminary adhesion function.
[0041] According to some embodiments of the present invention, the additives are one or more selected from guar gum powder, graphite, polytetrafluoroethylene, glycerin, glass fiber, and activated carbon. Specifically, one or more of the above-mentioned additives are used, and the specific selection can be adjusted according to the specific application requirements to achieve the best effect, thereby improving the extrusion smoothness of the mixed slurry.
[0042] Specifically, guar gum is a natural polymer compound often used as a thickener and suspending agent to increase the viscosity of slurries and prevent solid particles from settling; graphite has excellent lubricating properties, which helps reduce friction; PTFE is known for its extremely low coefficient of friction, and its addition to materials can significantly improve their wear resistance and self-lubricating properties; glycerin is a common humectant, and its addition to slurries can help retain the moisture in the materials, increasing their flexibility and ductility; glass fiber is a commonly used reinforcing material that can significantly improve the tensile strength, flexural strength, and impact toughness of composite materials; activated carbon particles can change the surface properties of the matrix material, such as reducing surface energy, making the material surface less prone to adhesion to other surfaces.
[0043] According to some embodiments of the present invention, the adhesive solvent is one or more of oxalic acid, citric acid, acetic acid, and ammonia water. Specifically, the adhesive solvent is mainly used to adjust the pH. Therefore, the adhesive solvent uses one or more of the above-mentioned solvents, which can be adjusted according to specific application requirements so that the pH value in the mixed solution can meet the optimal function of the organic adhesive, thereby improving the quality of subsequent products.
[0044] Oxalic acid is a strong organic acid with excellent complexing ability, especially for polyvalent metal ions. Therefore, using oxalic acid as a colloidal solvent helps prevent particle aggregation, thereby improving the uniformity and stability of the slurry. It also effectively lowers the pH value of the slurry, making the mixed slurry suitable for applications requiring an acidic environment. Citric acid is a weak acid; therefore, when adjusting the pH value of a solution, citric acid provides a buffering effect, neutralizing a certain amount of strong alkali or strong acid without causing drastic pH changes. This is crucial for applications requiring precise pH control. Citric acid also improves the dispersion of solid particles in the slurry, reducing aggregation and enhancing the slurry's fluidity and uniformity. Acetic acid is a weak acid suitable for fine-tuning the pH value of the slurry without drastically altering the environment, facilitating precise control of reaction conditions. Ammonia is a commonly used alkaline solution that effectively raises the pH value of the slurry, which is particularly important for materials or processes requiring an alkaline environment.
[0045] According to some embodiments of the present invention, a mixed slurry is prepared by placing a metal oxide precursor, an inorganic binder, an organic binder, an additive, and a solvent in a ball mill. The ball milling speed is 200 r / min-500 r / min, and the ball milling time is 10 min-30 min. This helps to ensure more thorough mixing of the mixed slurry, thereby further improving the uniformity of the active components of the formed catalyst.
[0046] For example, the ball milling speed can be 200 r / min, 300 r / min, 400 r / min or 500 r / min, and the ball milling time can be 10 min, 20 min or 30 min.
[0047] Optionally, the water content of the mixed slurry is between 10wt% and 40wt%, for example, the water content of the mixed slurry can be 10wt%, 20wt%, 30wt% or 40wt%.
[0048] According to some embodiments of the present invention, the drying temperature of the printed preform is 50 ℃-120 ℃, and the drying time is 2 h-8 h. This ensures that the printed preform dries more completely, thereby ensuring the solvent removal rate in the printed preform and further ensuring the structural stability of the final product.
[0049] For example, the drying temperature of the printed preform can be 50℃, 60℃, 70℃, 80℃, 90℃, 100℃, 110℃ or 120℃; the drying time can be 2h, 3h, 4h, 5h, 6h, 7h or 8h.
[0050] According to some embodiments of the present invention, the calcination temperature of the printed preform is 300℃-600℃, and the calcination time is 2-8h. This ensures the removal rate of organic binders or other impurities in the printed preform, thereby improving the mechanical properties of the final product.
[0051] For example, the calcination temperature of the printed preform can be 300℃, 400℃, 500℃ or 600℃; the calcination time can be 2h, 3h, 4h, 5h, 6h, 7h or 8h.
[0052] According to some embodiments of the present invention, such as Figures 2-3 As shown, step S1 includes: Step S11: Prepare an alkaline solution containing an alkali metal or alkaline earth metal; specifically, prepare an alkaline solution of a certain concentration, for example, an alkaline solution with a concentration of 0.1 mol / L to 2 mol / L can be prepared. The alkaline solution can be a sodium hydroxide solution, etc.
[0053] Step S12 involves adding the metal oxide support to the alkaline solution and stirring to obtain a mixture. Specifically, the metal oxide support serves as a support for the catalytically active component, providing high specific surface area, good thermal stability, and chemical stability. The metal oxide support can be manganese oxide, manganese dioxide, manganese trioxide, etc. The alkaline solution mainly functions to adjust the pH value, promote the hydrolysis and nucleation of metal species, and introduce alkali metal or alkaline earth metal elements for doping, thereby altering the surface properties of the metal oxide support.
[0054] It should be noted that when adding the metal oxide support to an alkaline solution, it needs to be stirred at a specific temperature for a specific time. For example, the stirring temperature should be between 40℃ and 90℃, and the stirring time between 0.5h and 2h. This allows the metal oxide support to fully contact the solution, achieving uniform impregnation or adsorption.
[0055] Step S13: The mixture is placed in a hydrothermal reactor for hydrothermal reaction to obtain reactants; wherein the reactants are a mixture of metal oxide precursor and solvent.
[0056] In step S14, the reactants are filtered and dried to obtain the metal oxide precursor. Specifically, the metal oxide precursor is a modified metal oxide support, whose morphology and internal structure have been altered, resulting in superior microstructure and surface properties. This not only provides more active sites but also significantly improves the catalyst's stability, low-temperature activity, and oxidation performance.
[0057] According to some embodiments of the present invention, the alkaline solution for alkali metals or alkaline earth metals is one or more selected from sodium hydroxide solution, potassium hydroxide solution, rubidium hydroxide solution, cesium hydroxide solution, strontium hydroxide solution, and barium hydroxide solution. Specifically, the various alkaline solutions described above play different roles in the preparation of metal oxide precursors. For example, sodium hydroxide solution can promote crystallization and increase specific surface area. Therefore, the selection of one or more of the above-mentioned solutions for the alkaline solution of alkali metals or alkaline earth metals can be made according to the actual needs of the catalyst, thereby ensuring high-quality printing results.
[0058] According to some embodiments of the present invention, the metal oxide support is one or more of manganese oxide, manganese dioxide, manganese trioxide, manganese tetroxide, and manganese pentaoxide. It should be noted that the above-mentioned metal oxides are all manganese oxides, which have strong redox properties, thereby effectively improving reactant diffusion and contact restriction in catalytic oxidation reactions, and thus enhancing the catalytic performance of the catalyst.
[0059] According to a second aspect of the present invention, a 3D-printed ultra-low temperature flue gas denitrification catalyst is prepared by the preparation method according to a first aspect of the present invention.
[0060] The 3D-printed ultra-low temperature flue gas denitrification catalyst according to embodiments of the present invention, prepared by the above-described method, can ensure the uniform distribution of the active components of the catalyst, thereby improving the catalytic performance and stability of the catalyst; at the same time, it can also make the catalyst exhibit extremely high stability, not only remaining stable under high-speed airflow purging, but also resisting external impacts and not easily broken, thus enabling the catalyst to adapt to various reaction conditions and process requirements, improving the applicability of the catalyst.
[0061] According to some embodiments of the present invention, the catalyst is a spherical, cylindrical, flake, or columnar particle. It is understood that the catalyst can be spherical, cylindrical, flake, or columnar, and the specific shape can be designed according to the actual application location, thereby enabling the catalyst to adapt to different reaction conditions and process requirements.
[0062] According to some embodiments of the present invention, the diameter of the catalyst is 2 mm-9 mm. This allows the catalyst to maintain strength and wear resistance while preventing it from becoming too large, thus enabling it to be packed into equipment of various sizes and improving its adaptability.
[0063] For example, the diameter of the catalyst can be 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm or 9 mm.
[0064] According to some embodiments of the present invention, the length of the catalyst is 5 mm-10 mm. This ensures that the catalyst has sufficient strength and wear resistance while preventing it from becoming too large, thus allowing it to be packed into equipment of various sizes and improving its adaptability.
[0065] For example, the diameter of the catalyst can be 5 mm, 6 mm, 7 mm, 8 mm, 9 mm or 10 mm.
[0066] A reactor according to a third aspect of the present invention includes a fixed-bed reactor or a fluidized-bed reactor and a catalyst according to a second aspect of the present invention, the catalyst being used to pack the fixed-bed reactor or the fluidized-bed reactor.
[0067] Understandably, catalysts can be packed in both fixed-bed and fluidized-bed reactors. It should be noted that catalysts can be packed in either fixed-bed or fluidized-bed reactors for cryogenic flue gas denitrification reactions.
[0068] Among them, a fixed-bed reactor is a reactor in which the catalyst remains stationary during the reaction process; a fluidized-bed reactor achieves the fluidization of the catalyst layer by allowing gas or liquid to pass through solid catalyst particles at a sufficient velocity; that is, the two reactors have different working principles. Therefore, the catalyst is used to pack the fixed-bed reactor or the fluidized-bed reactor. Thus, the catalyst of the embodiments of this application can adapt to a variety of reaction conditions and process requirements.
[0069] According to the reactor of the present invention, by filling it with the above-mentioned catalyst, the stability and reliability of the entire process can be improved, and the frequency of catalyst replacement can be reduced, thereby reducing maintenance costs.
[0070] The following is for reference. Figures 1-3 The present invention describes a method for preparing a 3D-printed ultra-low temperature flue gas denitrification catalyst based on three specific embodiments.
[0071] Example 1, Preparation methods include: The carrier manganese octoxide was added to a 0.5 mol / L sodium hydroxide solution and stirred thoroughly at 80°C for 1 h. The mixture was then placed in a hydrothermal reactor and reacted at 160°C for 12 h. Finally, the mixture obtained after the hydrothermal reaction was filtered and dried to obtain the metal oxide precursor.
[0072] 90 parts of metal oxide precursor, 2 parts of silica sol, 5 parts of carboxymethyl cellulose, 2 parts of guar gum powder, and 1 part of ammonia were selected. Then, 20 wt% of water was added to the mixture. The raw materials were mixed by ball milling to prepare a slurry. The ball milling speed was 400 r / min and the ball milling time was 20 min.
[0073] The slurry was printed into a cylindrical preform with a diameter of 5 mm and a length of 8 mm using 3D printing direct writing technology. The printed preform was then dried at 100°C for 6 h and finally calcined at 300°C for 6 h to obtain a cylindrical integral granular catalyst.
[0074] Example 2, Preparation methods include: The carrier manganese trioxide was added to a 1 mol / L sodium hydroxide solution and stirred thoroughly at 80°C for 0.5 h. The mixture was then placed in a hydrothermal reactor and reacted at 180°C for 16 h. Finally, the mixture obtained after the hydrothermal reaction was filtered and dried to obtain the metal oxide precursor.
[0075] 86 parts of metal oxide precursor, 2 parts of silica sol, 8 parts of carboxymethyl cellulose, 2 parts of guar gum powder, and 2 parts of sodium hydroxide were selected, and then 30 wt% of water was added to the mixture. The above raw materials were mixed by ball milling to prepare a mixed slurry, wherein the ball milling speed was 300 r / min and the ball milling time was 30 min.
[0076] The slurry was printed into a cylindrical preform with a diameter of 3 mm and a length of 10 mm using 3D printing direct writing technology. The preform was then dried at 100°C for 8 h and finally calcined at 400°C for 6 h to obtain a cylindrical integral granular catalyst.
[0077] Example 3, Preparation methods include: The carrier manganese trioxide was added to a 0.5 mol / L potassium hydroxide solution and stirred thoroughly at 80°C for 1 h. The mixture was then placed in a hydrothermal reactor and reacted at 160°C for 16 h. Finally, the mixture obtained after the hydrothermal reaction was filtered and dried to obtain the metal oxide precursor.
[0078] 80 parts of metal oxide precursor, 4 parts of halloysite nanotubes, 8 parts of polyethylene glycol, 4 parts of guar gum powder, and 4 parts of ammonia were selected. Then, 30 wt% of water was added to the mixture. The above raw materials were mixed by ball milling to prepare a slurry. The ball milling speed was 300 r / min and the ball milling time was 30 min.
[0079] The slurry was printed into a spherical preform with a diameter of 5 mm using 3D printing direct writing technology. The preform was then dried at 100°C for 8 h and finally calcined at 350°C for 6 h to obtain a cylindrical integral granular catalyst.
[0080] Example 4, Preparation methods include: The carrier manganese octoxide was added to a 0.5 mol / L barium hydroxide solution and stirred thoroughly at 80°C for 1 h. The mixture was then placed in a hydrothermal reactor and reacted at 160°C for 16 h. Finally, the mixture obtained after the hydrothermal reaction was filtered and dried to obtain the metal oxide precursor.
[0081] 88 parts of metal oxide precursor, 2 parts of kaolin, 6 parts of polyethylene glycol, 2 parts of guar gum powder, and 2 parts of ammonia were selected. Then, 15 wt% of water was added to the mixture. The above raw materials were mixed by ball milling to prepare a slurry. The ball milling speed was 400 r / min and the ball milling time was 30 min.
[0082] The slurry was printed into a cylindrical preform with a diameter of 5 mm using 3D printing direct writing technology. The monolithic granular catalyst preform was then dried at 100°C for 8 h and finally calcined at 400°C for 6 h to obtain the cylindrical monolithic granular catalyst.
[0083] Example 5, Preparation methods include: The carrier manganese octoxide was added to a 0.5 mol / L barium hydroxide solution and stirred thoroughly at 80°C for 1 h. The mixture was then placed in a hydrothermal reactor and reacted at 160°C for 16 h. Finally, the mixture obtained after the hydrothermal reaction was filtered and dried to obtain the metal oxide precursor.
[0084] 75 parts of metal oxide precursor, 4 parts of kaolin, 13 parts of polyethylene glycol, 4 parts of guar gum powder, and 4 parts of ammonia were selected. Then, 15 wt% of water was added to the mixture. The above raw materials were mixed by ball milling to prepare a slurry. The ball milling speed was 400 r / min and the ball milling time was 30 min.
[0085] The slurry was printed into a cylindrical preform with a diameter of 5 mm using 3D printing direct writing technology. The monolithic granular catalyst preform was then dried at 100°C for 8 h and finally calcined at 400°C for 6 h to obtain the cylindrical monolithic granular catalyst.
[0086] In the description of this invention, it should be understood that the terms "center," "longitudinal," "lateral," "length," "width," "thickness," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," "outer," "clockwise," "counterclockwise," "axial," "radial," and "circumferential" indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are used only for the convenience of describing this invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on this invention.
[0087] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this invention, "a plurality of" means two or more, unless otherwise explicitly specified.
[0088] In this invention, unless otherwise explicitly specified and limited, the terms "installation," "connection," "linking," and "fixing," etc., should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a mechanical connection, an electrical connection, or a communication connection; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components. Those skilled in the art can understand the specific meaning of the above terms in this invention according to the specific circumstances.
[0089] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0090] Although embodiments of the invention have been shown and described, those skilled in the art will understand that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the claims and their equivalents.
Claims
1. A method for preparing a catalyst for ultra-low temperature flue gas denitrification based on 3D printing, characterized in that, The preparation method includes: Step S11: Prepare an alkaline solution containing alkali metals or alkaline earth metals; Step S12: Add the metal oxide support to the alkaline solution and stir to mix, obtaining a mixture; Step S13: The mixture is placed in a hydrothermal reactor to carry out a hydrothermal reaction to obtain reactants; Step S14: The reactants are filtered and dried to obtain a metal oxide precursor; Step S2: Prepare a mixed slurry based on metal oxide precursor, inorganic binder, organic binder, additives and adhesive solvent; Step S3: The mixed slurry is printed into a shape using 3D printing direct writing technology to obtain a printed preform; Step S4: The printed preform is dried and calcined to obtain a catalyst.
2. The preparation method of the 3D-printed ultra-low temperature flue gas denitrification catalyst according to claim 1, characterized in that, The mixed slurry, by weight, comprises: 70-90 parts of metal oxide precursor; 2-5 parts of inorganic binder; 5-15 parts of organic binder; 2-5 parts of additives; and 1-5 parts of adhesive solvent.
3. The preparation method of the 3D-printed ultra-low temperature flue gas denitrification catalyst according to any one of claims 1-2, characterized in that, The inorganic binder is one or more selected from aluminum sol, silica sol, sodium silicate, halloysite nanotubes, bentonite, and kaolin; and / or, The organic binder is one or more selected from polyvinyl alcohol, polyethylene glycol, polyacrylamide, carboxymethyl cellulose, and starch; and / or, The additives are one or more selected from guar gum powder, graphite, polytetrafluoroethylene, glycerin, glass fiber, and activated carbon; and / or, The adhesive solvent is one or more of oxalic acid, citric acid, acetic acid, and ammonia.
4. The preparation method of the 3D-printed ultra-low temperature flue gas denitrification catalyst according to claim 1, characterized in that, The metal oxide precursor, the inorganic binder, the organic binder, the additives, and the adhesive solvent are placed in a ball mill to prepare a mixed slurry. The ball milling speed is 200 r / min-500 r / min, and the ball milling time is 10 min-30 min.
5. The preparation method of the 3D-printed ultra-low temperature flue gas denitrification catalyst according to claim 1, characterized in that, The drying temperature of the printed preform is 50 ℃-120 ℃, and the drying time is 2h-8h; the calcination temperature of the printed preform is 300℃-600 ℃, and the calcination time is 2-8h.
6. The preparation method of the 3D-printed ultra-low temperature flue gas denitrification catalyst according to claim 1, characterized in that, The alkaline solution of the alkali metal or alkaline earth metal is one or more selected from sodium hydroxide solution, potassium hydroxide solution, rubidium hydroxide solution, cesium hydroxide solution, strontium hydroxide solution, and barium hydroxide solution; and / or, The metal oxide carrier is one or more of manganese oxide, manganese dioxide, manganese trioxide, manganese tetroxide, and manganese pentoxide.
7. A catalyst for ultra-low temperature flue gas denitrification based on 3D printing, characterized in that, The catalyst is prepared by the preparation method according to any one of claims 1-6.
8. The catalyst for ultra-low temperature flue gas denitrification based on 3D printing according to claim 7, characterized in that, The catalyst is a spherical, flake, or columnar particle, and / or the diameter of the catalyst is 2 mm to 9 mm, and / or the length of the catalyst is 5 mm to 10 mm.
9. A reactor, characterized in that, include: A fixed bed or a fluidized bed and a catalyst according to any one of claims 7-8, the catalyst being used to pack the fixed bed or the fluidized bed.
Citation Information
Patent Citations
Method for 3D printing of monolithic catalyst
CN112058317A
Manganese-containing denitration catalyst and preparation method thereof
CN119215883A